Chemical constituents from the leaves of Craibiodendron yunnanense and their chemotaxonomic significance. (December 2022) - Liu, Na; Sun, Yilin; Sun, Yulin; Sun, Yajie; Yang, Fengying; Wang, Peng; Bermudez, Ramon Santos; Ge, Di
Abstract: The phytochemical investigation on the leaves of Craibiodendron yunnanense W.W. Smith resulted in the isolation of 21 compounds, including 11 known ursane triterpenes, 8 oleanane triterpenes, and 2 sterols. Their structures were clarified by analyses of their NMR spectroscopic data as well as by comparison of these data with those published in the literature. From the present investigation, compounds 1 –2, 6, 8 –10, 13 –16, 18 and 21 were isolated for the first time from the family Ericaceae, and their chemotaxonomic significance was discussed. Additionally, compounds 21 exhibited in vitro cytotoxicity against human MDA-MB-231 and BT-549 cancer cell lines with IC50 value of 14.19 μM and 21.45 μM, respectively. Highlights: Nineteen triterpenes and two sterols were isolated from Craibiodendron yunnanense. The isolates were evaluated for their cytotoxic activities. The chemotaxonomic significance of the isolated compounds was summarized.